The Effect of Collaborative Learning on Students’ Mathematical Communication and Problem-Solving Skills in Polyhedra - Emilia; Fadrik Adi Fahrudin; Baiq Rofina Arvy (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
This study aims to determine the effect of the Collaborative Learning model on students’ mathematical communication skills and mathematical problem-solving skills in the topic of polyhedra (three-dimensional shapes with flat surfaces). This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group pretest–posttest design. The population of the study consisted of all eighth-grade students of MTs Manba’ul Ulum Dasan Ketujur, West Lombok. The sample comprised two classes selected through cluster random sampling, namely one experimental class and one control class, each consisting of 30 students. The research instrument was an essay test used to measure students’ mathematical communication skills and mathematical problem-solving skills. The data were analyzed using descriptive and inferential statistics, including the normality test, homogeneity test, independent samples t-test, and MANOVA test with the assistance of SPSS software. The results of the study indicate that students’ mathematical communication skills and mathematical problem-solving skills in the experimental class improved more significantly than those in the control class. The results of the independent samples t-test revealed a significant difference between the experimental and control classes. Furthermore, the MANOVA test results showed that the Collaborative Learning model simultaneously had a significant effect on improving students’ mathematical communication skills and mathematical problem-solving skills in the topic of polyhedra. The novelty of this study lies in examining the effectiveness of the Collaborative Learning model in improving two mathematical abilities simultaneously, namely mathematical communication skills and mathematical problem-solving skills on the topic of polyhedra (three-dimensional shapes with flat surfaces) using a multivariate analysis approach (MANOVA).